Ethics and health: two questions, two assignments. - Carrasco de Paula, Ignacio (Medicina e Morale, 2002)
Ethics and health, also being two component of every single man, are often read like incompatible realities. The right to health occupies a place of relief among the conquests of the modernity, yet, despite the well known definition of health of WHO. This definition is aimed to specify, more than a reality, a power of intervention by the same institution, it is still necessary to clarify what identifying with such right in the practice. It doesn't concern mere survival, but even the enjoyment of the somatic and functional fullness of own body, and however it cannot be put aside by also considering in this context the spiritual comfort of the person. The centre of the attention must be set on the suffering man; besides, it becomes priority to face the threat of the discrimination in the access to the essential services for the defence of health. This last aspect is set like a issue of justice and it is gambled away to two levels: 1. the level of commutative justice, in the context of a physician-patient relationship reduced merely to contractual professional performance more than on a real communication; 2. the issue of distributive justice that provides for that to everybody is given how much it is up to him. It must be driven by the principle of subsidiarity, where the benefit doesn't owe a substitute, because it becomes impossible for the State to satisfy the needs of everybody. In the allocation of resources, the respect of distributive justice is gambled away to three levels of very precise responsibility: the health policies, the medical profession and the management of the local resources and services. However, the purpose of the common good finds a limit in the centrality and preciousness of every single person, healthy or sick, whose dignity represents an impassable limit, even in the name of justice.